Comparative tribological investigation of castor oil and its transesterified and aminolyzed derivatives - Lasch, G (2024)
This study compared the tribological performance of castor oil (CO), its transesterified (TCO), and aminolyzed (ACO) forms. A limited number of research articles are available regarding the tribological properties of these modified forms, especially the aminolyzed. Assessments included film thickness, piezoviscosity, Stribeck curve, and scuffing resistance. The film thickness followed the same order of the dynamic viscosity, i.e.: CO > ACO > TCO. The chemical modifications reduced the piezoviscosity, which was estimated as following: CO > TCO > ACO. ACO exhibited the lowest coefficient of friction (CoF) in the mixed and boundary regimes. ACO with a strong adsorbed film and lower piezoviscosity (consequently stable viscosity and reduced heating) demonstrated superior tribological properties (higher scuffing resistance and lower CoF).